PROFIL KOMPLIKASI DAN PENYULIT PADA IBU HAMIL DENGAN USIA DIBAWAH 20 TAHUN - Nita Tri Putri; Vedjia Medhyna; Nurul Amalina; Marini Oktavia MR (Universitas Fort de Kock Bukittinggi, 2023)
Around 31% of women gave birth to women under the age of 20 and UNICEF reports that 1.2 million Indonesian girls experience marriage under the age of 18. This study aims to determine the description of complications and barriers in pregnant women under the age of 20 years. This type of research is retrospective descriptive, the research was conducted at Kolonel Abundjani Regional Hospital Bangko, Merangin Regency in April-May 2022. The study population was all pregnant women under 20 years of age in 2019-2021, a sample of 357 people, using total sampling technique. The instrument used was a data reduplication list and analyzed by describing the independent variables. The results obtained that there are 216 people (60.5%) of respondents in pregnant women under the age of 20 years did not experience complications and barriers, and the most types of complications and barriers were abortion, as many as 57 people (16.0%). From the results of the study, it was concluded that the complications and barriers that occurred in pregnancies under 20 years were 39.5%. Efforts that need to be done are providing information about the impact of pregnancy at the age of < 20 years for teenagers, for mothers who are pregnant in their teens to perform ANC at least 6 times during pregnancy, promotive and preventive efforts need to be increased and involve cross-sectoral roles in delaying pregnancies under 20 years of age.Keywords: Complications and barriers, Pregnant Women < 20 Years